2016
DOI: 10.1136/jnnp-2016-313793
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cigarette smoking on ALS outcome: a population-based study

Abstract: This study has demonstrated in a large population-based cohort of patients with ALS that cigarette smoking is an independent negative prognostic factor for survival, with a dose-response gradient. Its effect is not related to the presence of COPD or to respiratory status at time of diagnosis. The understanding of the mechanisms, either genetic or epigenetic, through which exogenous factors influence disease phenotype is of major importance towards a more focused approach to cure ALS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 29 publications
4
22
2
Order By: Relevance
“…The positive association we found between ALS and smoking habits is consistent with previous studies [42,[45][46][47][48][49][50][51][52][53]. Despite a few studies reporting no difference or a decreasing risk in association with smoking [43,54,55], nevertheless, a detrimental effect of smoking has also been reported as a negative prognostic factor [56,57]. This strengths the relevance of quitting in either preventing the onset or delaying the progression of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…The positive association we found between ALS and smoking habits is consistent with previous studies [42,[45][46][47][48][49][50][51][52][53]. Despite a few studies reporting no difference or a decreasing risk in association with smoking [43,54,55], nevertheless, a detrimental effect of smoking has also been reported as a negative prognostic factor [56,57]. This strengths the relevance of quitting in either preventing the onset or delaying the progression of the disease.…”
Section: Discussionsupporting
confidence: 91%
“…Clinical predictors were sex, site of onset (spinal vs bulbar), age at onset of weakness or bulbar symptoms, revised El Escorial criteria (definite vs probable or possible ALS), 12 diagnostic delay (time from onset of weakness or bulbar symptoms to diagnosis), forced vital capacity (FVC; percentage of predicted based on normative values for age, sex, and body height), progression rate defined by the slope on the revised ALS Functional Rating Scale (ALSFRS-R), 15 premorbid body-mass index (BMI), 16 current smoking, 17 and cigarette pack-years. 6 Cognitive predictors were the presence of frontotemporal dementia according to the Neary or Rascovsky criteria, 18 and scores on the verbal fluency index, 19 the Frontal Assessment Battery, 20 and the ALS Frontotemporal Dementia Questionnaire (ALSFTD-Q).…”
Section: Methodsmentioning
confidence: 99%
“…Patients who live long enough to attend a specialist research clinic are different from those identified in population studies, and this difference can cause bias in the results. For instance, smok- ing has been shown to shorten survival in a population study, 67 so a case-control study selecting participants from clinics would find smokers underrepresented in the ALS group and would thus suggest that smoking either has no effect or might be protective. Similarly, ALS specialists report anecdotally that their patients tend to be athletic, slim, and very fit, 68 but if these factors slow disease progression rather than increase risk, such patients will be overrepresented at specialist centers.…”
Section: Insights Into Sporadic Alsmentioning
confidence: 99%